Effect of enzymatic pre-treatment on thermophilic composting of shrimp pond sludge to improve ammonia recovery - Zainul Kamal, Syazni; Koyama, Mitsuhiko; Syukri, Fadhil; Toda, Tatsuki; Minh Tran, Quyen Ngoc; Nakasaki, Kiyohiko (Elsevier, 2022)
In recent years, attempts have been made to develop a thermophilic composting process for organic sludge to produce ammonia gas for high value-added algal production. However, the hydrolysis of non-dissolved organic nitrogen in sludge is a bottleneck for ammonia conversion. The aim of this study was to identify enzymes that enhance sludge hydrolysis in a thermophilic composting system for ammonia recovery from shrimp pond sludge. This was achieved by screening useful enzymes to degrade non-dissolved nitrogen and subsequently investigating their effectiveness in lab-scale composting systems. Among the four hydrolytic enzyme classes assessed (lysozyme, protease, phospholipase, and collagenase), proteases from Streptomyces griseus were the most effective at hydrolysing non-dissolved nitrogen in the sludge. After composting sludge pre-treated with proteases, the final amount of non-dissolved nitrogen was 46.2% of the total N in the control sample and 22.3% of the total N in the protease sample, thus increasing the ammonia (gaseous and in-compost) conversion efficiency from 41.5% to 56.4% of the total N. The decrease in non-dissolved nitrogen was greater in the protease sample than in the control sample during the pre-treatment period, and no difference was observed during the subsequent composting period. These results suggest that Streptomyces proteases hydrolyse the organic nitrogen fraction, which cannot be degraded by the bacterial community in the compost. Functional potential analysis of the bacterial community using PICRUSt2 suggested that 4 (EC:3.4.21.80, EC:3.4.21.81, EC:3.4.21.82, and EC:3.4.24.77) out of 13 endopeptidase genes in S. griseus were largely absent in the compost bacterial community and that they play a key role in the hydrolysis of non-dissolved nitrogen. This is the first study to identify the enzymes that enhance the hydrolysis of shrimp pond sludge and to show that the thermophilic bacterial community involved in composting has a low ability to secrete these enzymes.